Development of a Conceptual Framework and Management Guide for Sustainable Contract Manufacturing Companies in South Africa - Mahove, T.T.; Matope, S. (The South African Journal of Industrial Engineering, 2025)
Articles on manufacturing outsourcing focus largely on providing guidance to brand owners on how to select the manufacturing partner, on the benefits of outsourcing manufacturing, and how to manage the contract manufacturing relationship. However, there is a lack of frameworks that offer guidance to contract manufacturing companies to help them to set up and run manufacturing organisations that achieve sustainable success as strategic supply chain partners to the brand owners. In this study, informed by the design science research methodology, an artefact, a critical success factors conceptual framework and management guide for contract manufacturing companies to achieve sustainable success is introduced.